2013
DOI: 10.1186/1756-3305-6-357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate variability on Plasmodium vivax and Plasmodium falciparum malaria in Yunnan Province, China

Abstract: BackgroundMalaria remains a public health problem in the remote and poor area of Yunnan Province, China. Yunnan faces an increasing risk of imported malaria infections from Mekong river neighboring countries. This study aimed to identify the high risk area of malaria transmission in Yunnan Province, and to estimate the effects of climatic variability on the transmission of Plasmodium vivax and Plasmodium falciparum in the identified area.MethodsWe identified spatial clusters of malaria cases using spatial clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 41 publications
8
39
1
Order By: Relevance
“…This is consistent with previous studies [20, 48, 49]. This is the only area where the local P. falciparum cases were reported by several studies [9, 15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies [20, 48, 49]. This is the only area where the local P. falciparum cases were reported by several studies [9, 15].…”
Section: Discussionsupporting
confidence: 93%
“…The cluster persisted for five years (2010–2014), contributing more than half the total number of P. vivax cases reported each year. Although the high-risk area identified in this area agrees with previous studies [20, 48, 49], a shift of the geographical location from Anhui to Yunnan province after 2009 is new. The reduction in Anhui may be explained by intensive malaria control in the central China provinces [50].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mosquito densities varied from 0.05 to 3.00 females per trap per night, with strong seasonality in all sites and a density peak from June to August. Species richness peaked from April to August according to our previously reports (Bi et al, 2013b; Wang et al, 2015; Yu et al, 2013). …”
Section: Discussionsupporting
confidence: 62%
“…1) when there were 3078 cases reported, most being concentrated in the southwest region—Yunnan Province, central and east region—Anhui, Henan and Jiangsu provinces [6]. Possible reasons for this re-emergence may include meteorological factors, climate change, increased mosquitoes and imported cases, as studies in China have indicated that these factors could have impacts on the transmission of malaria [10, 1214]. Given the high-density population, rapid economic development, urbanization and increasing numbers of international travelers in China, there is an urgent need to understand the effectiveness of current infectious disease control and prevention of malaria in the face of climate change.
Fig.
…”
Section: Introductionmentioning
confidence: 99%